Pembuatan papan partikel berbasis kulit tanduk kopi dan tandan kosong kelapa sawit - Aisyah, Siti; Mulyara, Budi; Adini, Izmi; Purwanto, Heri (AGROINTEK, 2025)
The palm oil industry produces solid waste, particularly empty oil palm fruit bunches. The lignin contained in these empty bunches functions to make the wood resistant to microbial attack. Meanwhile, coffee horn skin waste is not used optimally. This research aims to utilize waste coffee horn skin and empty oil palm fruit bunches as alternative raw materials for making particle boards. Empty oil palm bunches and coffee husks are dried in the sun to reduce the water content of products and ensure the fiber becomes dry. Empty bunches and dried horn skin are then soaked using a mixture of NaOH and distilled water. The resulting fibers that have been chopped are then dried. The resulting dried fibers are reduced in size again. There are 7 different ratios that are used in fiber mass between empty bunches plam fruit and coffee husk. Every particle board was built in dimensions of 25 x 25 x 5cm and pressed for 10 minutes. The research results obtained in the form of board particle density tests showed significant differences in all treatments, and the density test results met SNI 03-2105-2006. Apart from that, there is no real difference in the test results for the particle board water content, so it meets SNI 03-2105-2006. Tests for the development of thick board particles showed that there were significant differences in all ratios, namely that P1, P2, P5 met SNI 03-2105-2006 and P3, P4, P6, P7 did not meet SNI 03-2105-2006. In the elastic modulus and fracture modulus tests, there were no differences in all treatments. However, they did not meet SNI 03-2105-2006, whereas, in the particle board absorbency test, there were significant differences in all treatments and the absorbency test results were still relatively high. However, SNI 03-2105-2006 does not specify standard values for air absorbency.